A Comparative Study on In-Class Assessment Practices by EFL Teachers in Uganda and Indonesia - Wanale Salama; Sri Setyarini; Pupung Purnawarman (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2025)
This comparative study investigates in-class assessment practices among secondary school EFL teachers in Uganda and Indonesia, guided by Vygotsky’s Sociocultural Theory of learning. The study explores commonly used assessment strategies, teachers’ perceptions of their effectiveness, and the key implementation challenges in both countries. A quantitative research design was employed, and data were collected from 120 EFL teachers (60 from each country) using structured questionnaires with Likert-scale and multiple-choice items. Descriptive and inferential statistical analyses including means, standard deviations, and independent t-tests were conducted. The findings revealed significant differences in assessment approaches: Ugandan teachers predominantly used traditional techniques such as quizzes and oral questioning, while Indonesian teachers more frequently employed interactive, collaborative methods like peer assessment and project-based learning. Aligned with Vygotsky’s emphasis on social interaction and scaffolding, Indonesian teachers demonstrated higher assessment literacy and greater engagement with formative practices. Nevertheless, educators in both contexts recognized the value of in-class assessment in supporting language development and learner engagement. Shared challenges included large class sizes, limited time, and inadequate resources. Based on the findings, the study recommends culturally responsive professional development, structural policy reforms, increased investment in infrastructure, and cross-national collaboration. These steps aim to foster inclusive, dialogic assessment practices aligned with Vygotsky's principles in diverse EFL classrooms